2019
DOI: 10.18203/2320-6012.ijrms20190373
|View full text |Cite
|
Sign up to set email alerts
|

Tubular electrospun scaffolds tested in vivo for tissue engineering

Abstract: Tissue engineering has been widely used for its great variety of functions. It has been seen as a solution to satisfy the need for vascular substitutes like small diameter vessels, veins, and nerves. One of the most used methods is electrospinning, due to the fact that it allows the use of various polymers, sizes, mandrels and it can adjust the conditions to create personalized scaffolds. For the creation of scaffolds is fundamental to understand the advantages and disadvantages of each polymer, of this, will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Material selection is predominantly effective in imitating the physical, chemical, mechanical, and structural properties of the scaffolds 9 . In addition to allowing rapid endothelialization and cell proliferation; biocompatibility, cytocompatibility, slow degradation rate, excellent strength, and high elongation features make PCL an indispensable biopolymer 10‐13 . On the other hand, PLA is an aliphatic bio‐based polymer that is preferable in biomedical applications due to its biocompatibility, rapid biodegradability, lack of toxicity, high mechanical strength, and modulus 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Material selection is predominantly effective in imitating the physical, chemical, mechanical, and structural properties of the scaffolds 9 . In addition to allowing rapid endothelialization and cell proliferation; biocompatibility, cytocompatibility, slow degradation rate, excellent strength, and high elongation features make PCL an indispensable biopolymer 10‐13 . On the other hand, PLA is an aliphatic bio‐based polymer that is preferable in biomedical applications due to its biocompatibility, rapid biodegradability, lack of toxicity, high mechanical strength, and modulus 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to allowing rapid endothelialization and cell proliferation; biocompatibility, cytocompatibility, slow degradation rate, excellent strength, and high elongation features make PCL an indispensable biopolymer 10‐13 . On the other hand, PLA is an aliphatic bio‐based polymer that is preferable in biomedical applications due to its biocompatibility, rapid biodegradability, lack of toxicity, high mechanical strength, and modulus 13‐15 . Furthermore, PLA has a high glass transition temperature ( T g : 55–60 ° C) which makes it more brittle and stiffer compared to PCL ( T g : − 60 ° C).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] PCL is a beneficial biopolymer for recellularization on living tissue due to its slow degradation rate which makes it suitable for tissue engineering applications. [18] Yalcin et al reported a study in which the design criteria were chosen to produce a biodegradable small-caliber vascular graft structure and resemble the native vascular system in morphological, mechanical, and biological aspects. PCL (45,000 Mn) and chloroform/ ethanol (9/1 v/v) solvent system were used for preparing the solution, which had an 18 w/v% concentration.…”
mentioning
confidence: 99%